Комплексне постачання вогнетривких виробів для металургії як ефективний фактор зниження питомих витрат - Шарандін, К. М.; Рябий, Д. В.; Смірнов, Юрій; Васильєв, Дмитро (Physico-technological Institute of Metals and Alloys, 2023)
Refractory lining is an integral part of the construction of metallurgical units and needs constant improvement. The production of refractories in China exceeded the level of 50 % of the total production of refractories in the world, which, combined with the relatively low prices of Chinese refractories, determines the dominant position of refractories exported from the People’s Republic of China (PRC) on the market of Ukraine and Europe. To increase competitiveness, refractories suppliers offer comprehensive engineering solutions to meet changing customer requirements. At the same time, the specific consumption of refractory materials is reduced as a result of the acceleration of progress in the technology of their manufacture and improvement of the technology of application. On the other hand, the specific costs of applied refractories for renewable technologies of metallurgical production, including the use of raw materials of new quality, changing prices of raw materials, energy carriers, etc., are increasing. In these conditions, the competition between manufacturers (suppliers) and engineering structures in search of ways to satisfy the growing demands of consumers is intensifying. New and existing technologies for the production and use of refractory materials are being developed and modernized. The main goals of the "complex supply" strategy, which involves the consolidation of the efforts of various entities within the scope of providing the consumer with refractory linings and service under the condition of ensuring economic feasibility, are considered, in particular, with the help of accounting by the consumer as current, but hidden costs associated with the project implementation. The real value of refractories in integrated supply is most often determined by the optimal approach to the application of lining, taking into account the general life cycle of the use of refractory materials. The most informative indicator is TCO (Total Cost of Ownership). This is an accounting of the sum of direct and indirect costs borne by the owner of the refractory lining during the life cycle period.